Nanocoatings for ballistic applications: a review - Biradar, Anand; Arulvel, S.; Kandasamy, Jayakrishna; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Najeeb, Muhammad Imran; Gaff, Milan; Hui, David (Walter de Gruyter GmbH, 2023)
The manufacturing of ballistic impact-resistant (BIR) body armours has evolved over the years with the aim of reducing their weight and enhancing their energy absorbing capacity upon ballistic impacts. The incorporation of nanoparticles into advanced BIR body armour systems is considered one of the promising techniques. The methods employed in incorporating various nanoparticles in the manufacturing of textile-based body armour systems face a research gap in the optimisation of the associated parameters. This article discusses the mechanism involved in the energy absorption of composites and nanocomposites upon ballistic impact. The current review article highlights the chemical, physical, and mechanical properties of various nanoparticles incorporated into BIR body armour systems. BIR nanocomposites consisting of carbon nanotubes, graphene nanoplatelets, nano-silica, nanoclays, nano-alumina, etc., have been discussed herein. In addition, the significance of various techniques for the dispersion of these nanoparticles was also highlighted. Various methods, such as sol–gel, PVD, CVD, thermal spray, and electroless methods for coating the nanoparticles on the surface of the fibre/fabric were also discussed.